2017
DOI: 10.37358/rc.17.1.5398
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Stability of Heteropolyacid Catalysts Supported on MCM-41 Materials Synthesized by Ultrasonic Irradiation

Abstract: A series of solid acid catalyst of the Keggin-type 12-phosphotungstic acid, H3PW12O40, supported on ordered mesoporous silica MCM-41 were prepared by a simple and effective impregnation method. MCM-41 supports were synthesized in a relatively short time via a recently reported ultrasonic irradiation method. The synthesis sonication time has been systematically varied in order to investigate its influence on the structural order of the resulting materials. The prepared catalysts were characterized by nitrogen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Furthermore, the regular pore structure and tuneable pore size enables rapid diffusion of reactants and products through the pores to minimize consecutive reactions. Usually, tungsten HPAs, in particular 12-tungstophosphoric acid (H 3 PW 12 O 40 , HPW, TPA), are the catalysts of choice considering their stronger Brønsted acidity, lower oxidation potential and higher thermal stability [66][67][68][69][70][71].…”
Section: Mcm-41 As Support For Immobilization Heteropolyacidsmentioning
confidence: 99%
“…Furthermore, the regular pore structure and tuneable pore size enables rapid diffusion of reactants and products through the pores to minimize consecutive reactions. Usually, tungsten HPAs, in particular 12-tungstophosphoric acid (H 3 PW 12 O 40 , HPW, TPA), are the catalysts of choice considering their stronger Brønsted acidity, lower oxidation potential and higher thermal stability [66][67][68][69][70][71].…”
Section: Mcm-41 As Support For Immobilization Heteropolyacidsmentioning
confidence: 99%
“…MCM-41support were prepared by ultrasonic irradiation under basic environment and the HPW/MCM-41 catalysts were obtained by impregnating the heteropolyacid on the synthesized supports as described in detail elsewhere [47]. BET areas between 1435 and 460 m 2 g -1 , and pore volumes between 0.914 and 0.208 cm 3 g -1 were obtained for the samples when the HPW loading increased from 0 to 30 wt%.…”
Section: Experimental Part Chemicals and Catalystmentioning
confidence: 99%
“…We have recently prepared and characterized MCM-41 supports by ultrasonic irradiation under basic pH, used them to obtain HPW/MCM-41 catalysts, and demonstrated that the synthesized materials retained the characteristic MCM-41 mesoporous structure after impregnation of the active phase onto the mesoporous surface. Details on the synthesis route and characterization results of the HPW/ MCM-41 catalysts are given elsewhere [47].…”
mentioning
confidence: 99%